Rancang Bangun Sistem Informasi E-Konseling Berbasis Website melalui Rapid Applications Development (RAD) (Studi Kasus SCU Universitas Nusa Putra) - Anggun Fergina; Sarah Ayu Rahmawati; Any Elvia Jakfar (Teknik Informatika Universitas Pamulang, 2025)
Student mental health is an important aspect that needs special attention, especially amid academic pressures and complex social challenges. At Nusa Putra University, counseling services are still conducted manually using Google Forms, which causes various obstacles such as overlapping schedules, delays in processing, and low student participation. This condition risks reducing the effectiveness of services, prolonging case handling times, and discouraging students from utilizing counseling services. Therefore, a digital system is needed that can overcome these problems in a more efficient and structured manner. This study aims to develop a website-based e-counseling system to improve the efficiency, accessibility, and quality of counseling services. The Rapid Application Development (RAD) method was used in the development of the system with an iterative and participatory approach. The system is equipped with an automatic scheduling feature based on the FIFO (First In, First Out) algorithm for more orderly queue management and Websocket integration to support real-time online counseling sessions. The results of black-box testing with 10 scenarios showed 100% success in all main functions. In addition, beta testing involving 11 respondents (1 counselor and 10 students) resulted in an average satisfaction rate of 89.09%, with the highest appreciation for response speed (90.90%) and feature relevance (89.09%). These findings confirm that the system not only functions well technically, but is also positively received by users because it effectively improves the efficiency, convenience, and quality of counseling services in higher education.